Development of e-worksheet based on engineering design process for composition function material - Lutfi Cahya Kurniawan; Indah Wahyuni (Universitas Muhammadiyah Malang, 2024)
Mathematics learning poses several challenges, making the utilization of technology, particularly e-worksheets, a promising solution to offer a more interactive learning experience and bolster student success. This research aims to describe the validity, practicality, and effectiveness of using Engineering Design Process (EDP)-based e-worksheets in composition function material in high school. The research subjects are 35 eleventh graders at SMAN 1 Tegaldlimo, Banyuwangi, East Java. The Research and Development (R&D) utilized the ADDIE model and collected data through observation, interviews, and tests. The results of expert validation approval obtained a score of 83.33%, which indicates valid or reasonable to use but requires slight updates. The practical results obtained from the analysis of student questionnaires were 76.69%. The pretest and post-test values are analyzed using the Wilcoxon Test with a significance value of < 0.05. The utilization of EDP-based e-worksheets significantly influences composition function material in high school. The N-Gain score shows the mean value was 70.09 %, which is categorized as high (quite effective). Developing e-worksheets based on feedback from teachers and students, as well as further studies on their long-term influence on student learning outcomes, is needed.